Operation Protective Edge 2014: Justifikasi Israel terhadap Pelanggaran Hukum Internasional dalam Prinsip Just War - Sari, Dyah Lupita (UI Scholars Hub, 2018)
The 2014 Gaza War is the third largest armed conflict between Israel and Hamas in the Gaza Strip. After Hamas fired rockets and mortars into strategic areas of Israel, the latter launched Operation Protective Edge as a counterattack. The use of military force by both sides led to enormous collateral damage, especially in the Gaza Strip. Operation Protective Edge is considered by many to have violated International Humanitarian Law; its conduct is seen as inconsistent with the principles in Just War. In explaining why the violations of International Humanitarian Law in Operation Protective Edge can be justified by Israel, this study grounds its analysis on thorough examination of the principle of Just War. The paper argues that the following factors bolster Israel’s justification: 1. The strength of the the right to self-defense argument; 2. Depiction of Operation Protective Edge as a proportional military operation; 3. Predication of the war between Israel-Hamas as an asymmetric conflict; 4. U.S. support, which finds basis on UN Security Council resolutions.